Estudo da adoção das melhores práticas em TI ITIL e integração com a metodologia de gestão e avaliação de desempenho BSC - Rodrigues, Carlos Augusto Pestana (2006)
The present work is a study and proposal of integration of the best practical in Information Technology defined by international organization OGC (Office of Governant Commerce), assigned and defined in its methodology ITIL (IT Infrastructure Library), with the appraised methodology and the model of the Balanced Scorecard by Kaplan e Norton (1997), in what it says about the Governance of Information Technology and the current situation of the management and measurement about the results of the adoption of the best practical in Information Technology ITIL in the organizations. Each time, more and more organizations are showing as having the Information Technology of the strategical and necessary factor for the improvement of its performance and competitiveness in the world of the businesses. Although this strategical consideration and the more representative investments in Information Technology, nor always exists an evaluation of the results reached for Information Technology in the strategical performance of the organizations. It exist a great difficulty in the gauging and control of the products and services of Information Technology, at the same time where a consensus appears that the adoptions of the best practical in Information Technology produce the best ones resulted. Based in these premises, this work has the following objectives: to evaluate the current level of the adoption of the best practical in Information Technology ITIL in the organizations with operations in our country and to evaluate the management model BSC of strategical evaluation of performance as a possible instrument of measurement of the results of the adoption of the best practical of Information Technology ITIL. To support of the raised hypotheses, a field research between representatives companies with national performance, in some segments that use, provide products and/or services with Information Technology. The hypotheses had been tested through the analysis and comparison of the gotten results and as product and final contributions are presented a current scene of the corporative market of the organizations about how much to the integration of the best practical in Information Technology, methodology BSC and the current situation of measurement for the continuous gauging of the results of the adoption of the best practical ITIL by the organizations.